(untitled) (Journal of Engineering, 2008)
Aluminum-Silicon alloys, with soft lubricant metal, are considered to be one of the important tribological alloys which resist seizure. The effect of different lead percentages (1-20%Pb) that added to the modified eutectic Al-12%Si alloy on the wear rate and resistance was studied by sliding these alloys under dry sliding conditions on a carbon steel disc at different sliding distances (2.24-40.37 km). The results showed that the wear rate was decreased and wear resistance increased with increasing lead percentage of Al-12%Si alloy. Furthermore, wear rate was increased linearly with increasing sliding distance.